Investigation of jaundice. (November 2019) - Khan, Reenam S.; Houlihan, Diarmaid D.; Newsome, Philip N.
Abstract: Jaundice is a clinical sign that reflects an accumulation of bilirubin in the blood. It can result from increased bilirubin production, inability of the liver to conjugate bilirubin or failure to excrete bilirubin into the biliary tree. Appropriate investigation of jaundice starts with a history of associated symptoms, and risk factors for liver disease. Clinical examination should look for stigmata of chronic liver disease and signs of specific liver diseases. Initial blood tests should assess liver injury and synthetic function. A combination of urinalysis and the pattern of abnormal liver function tests can indicate whether the jaundice is likely to be hepatitic or cholestatic, and can guide further investigations. This review describes bilirubin metabolism, the causes of jaundice and the appropriate investigation of jaundice.